Facile spray-drying/pyrolysis synthesis of intertwined SiO@CNFs&G composites as superior anode materials for Li-ion batteries - Hou, X.; Wang, J.; Zhang, M.; Liu, X.; Shao, Zongping; Li, W.; Hu, S. (Royal Society of Chemistry, 2014)
A silicon monoxide/carbon nanofibers/graphite (SiO@CNFs&G) composite with outstanding electrochemistry performance has been easily synthesized using a simple method based on spray drying in combination with a subsequent pyrolysis process; carbon nanofibers intertwined with carbon coated silicon monoxide spherical composites and embedded micron-sized graphite. The combination of twisted carbon nanofibers, graphite and amorphous carbon-coating layer accommodates the large volume change of silicon during the lithium intercalation/extraction process, which stabilizes electrode structure during discharge-charge cycles. As an anode material, the as-obtained SiO@CNFs&G composite demonstrates high capacity and excellent cycle stability. An initial specific discharge capacity of approximately 1031.7 mA h g-1 with a coulombic efficiency of 56.6% and a reversible specific capacity of approximately 615.1 mA h g-1 after 100 cycles at a constant density of 100 mA g-1 is achieved, which is about two times the values for graphite. Because of the facile synthesis process and fascinating performance of the prepared electrode, significant commercial potential is expected.